PERENCANAAN MANAJEMEN PEMELIHARAAN BANGUNAN HOTEL X DI PADANG UNTUK MENCAPAI EFISIENSI BIAYA DAN WAKTU - Muhammad Ilham Maulana; Hanif Sufran; Merley Misriani; Rahmi Hidayati; Jumyetti Jumyetti (Racic : Rab Construction Research, 2024)
Every building needs maintenance on every component of the building. Before carrying out maintenance activities, planning is required for every aspect of maintenance in the building. Good planning can ensure achieving goals in carrying out maintenance that utilizes costs and time efficiently. This study aims to plan the implementation of hotel building maintenance to achieve cost efficiency and maintenance time. The implementation methods include making SOPs, checklist forms, cost planning and maintenance schedules. Planning for SOP is made by adding existing SOP from the hotel to several SOPs from ministerial regulations that the hotel has not implemented. Planning checklist forms, costs and maintenance schedules made for architectural, mechanical and electrical work are limited to a period of 1 year and use ministerial regulation no. 24/PRT/M/2008 to check its suitability with implementation in the field. This research shows that hotel building maintenance management planning is better than before. The maintenance management plan created is expected to help the hotel carry out maintenance activities efficiently and utilize costs and time.